HIV status, burden of comorbid disease, and biomarkers of inflammation, altered coagulation, and monocyte activation. - Armah, Kaku A; McGinnis, Kathleen; Baker, Jason; Gibert, Cynthia; Butt, Adeel A; Bryant, Kendall J; Goetz, Matthew; Tracy, Russell; Oursler, Krisann K; Rimland, David; Crothers, Kristina; Rodriguez-Barradas, Maria; et al. (Clinical infectious diseases : an official publication of the Infectious Diseases Society of America, 2012)
Biomarkers of inflammation, altered coagulation, and monocyte activation are associated with mortality and cardiovascular disease (CVD) in the general population and among human immunodeficiency virus (HIV)-infected people. We compared biomarkers for inflammation, altered coagulation, and monocyte activation between HIV-infected and uninfected people in the Veterans Aging Cohort Study (VACS).
Keywords: Adult; Aged; Antigens, CD14; Biological Markers; Blood Coagulation Disorders; Cohort Studies; Comorbidity; Female; Fibrin Fibrinogen Degradation Products; HIV Infections; Humans; Inflammation; Interleukin-6; Logistic Models; Male; Middle Aged; Monocytes; Veterans